Designing a web-based virtual environment for 3D cadaster - Javad Sadidi; Sabah Motamedi; hani rezayan (تحقیقات کاربردی علوم جغرافیایی)
Complexity of multi dimension developments and infrastructures intensifies the land related challenges to adopt legal laws, restrictions and responsibilities.  Although, multi dimension estates have been registering for many years, as the complexity of the estates are increased, disadvantages of the 2D cadaster is more appeared. Hence, the 3D cadaster has been a necessity for sustainable development. Visualizing is one of the important components of 3D cadaster. In the current research, for efficient and effective visualization of land ownerships and their related 3D information, firstly, the needed essentials of cadaster visualization systems have been classified into 3 groups including: cadaster, visualization and independent properties. Then, the trends of 3D visualization developments for older plugin and WebGL based technologies have been considered. Finally, a number of the most important systems according to the needed criteria for web-based 3D cadaster were evaluated and consequently, Cesium virtual environment has been selected as the best for the development purpose. To develop a system for 3D cadaster visualization, 2D building properties was converted to 3D using different software and then, land law properties were added and subsequently, Building Information Model (BIM) was provided. HTML5, JavaScript and CSS languages along with WebGL library and Cesium API were utilized. The implemented service is able to display WFS-based standard vector layers as well as WMS image of OGC standard. The system has the possibilities of 3D visualization like web-based 3D cadaster visualization and land law properties over the web. This enables the user to make the printed output of BIM along with descriptive information of the buildings.